2016
DOI: 10.1111/dar.12420
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among men and women who use methamphetamine: A mixed‐methods study in South Africa

Abstract: Introduction The prevalence of methamphetamine use has risen dramatically in parts of South Africa. Globally, methamphetamine has been linked to intimate partner violence (IPV) and other forms of aggression. The aim of this mixed-methods study was to examine the experiences of physical IPV and its contextual factors among methamphetamine users in an urban community in Cape Town, South Africa. Methods Active methamphetamine users were recruited using respondent driven sampling. All participants (n=360) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
4
22
0
3
Order By: Relevance
“… illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV . There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma . However, Madruga et al .…”
supporting
confidence: 81%
See 3 more Smart Citations
“… illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV . There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma . However, Madruga et al .…”
supporting
confidence: 81%
“…Gilchrist et al [18] illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV [19]. There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma [20,21]. However, Madruga et al [22] found that although witnessing parental violence was independently associated with being a victim of IPV, IPV perpetration was not associated with witnessing parental violence when experience of direct violence as a child was controlled for.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…神兴奋剂,具有很强的精神毒性和神经破坏作用,对成瘾者的身体、行为和精神等方面都会产生一系列 的破坏性反应,包括心血管和呼吸问题、抽搐、牙齿和皮肤溃烂、攻击行为、冒险寻求、性冲动、各类 精神疾病以及记忆力下降等 (Winslow, Voorhees, & Pehl, 1988;Watt, Guidera, Hobkirk, Skinner, & Meade, 2016;Colfax & Shoptaw, 2005)。其中,攻击或暴力行为是冰毒成瘾者较为突出的行为表现,国内外众多 研究结果支持滥用冰毒会导致成瘾者产生高水平的暴力和攻击行为 (Boles, & Miotto, 2003;Cartier, Farabee, & Prendergast, 2006;王玮,肇恒伟,李晨,赵子阳,2017) …”
Section: 引言 冰毒(即甲基苯丙胺,又名脱氧黄麻碱,Methamphetamine)属于苯丙胺类的兴奋剂,是当前流行较为 广泛的一unclassified